The Kabbalistic scholars of the Antwerp Polyglot Bible - Wilkinson, Robert J. (Studies in the history of Christian traditions, 2007)
The Spanish tradition: the notion of a Polyglot -- The Spanish tradition : Hebrew studies and Kabbalistic infuence -- The Northern scholars : Masius -- The Northern scholars : the role of Postel in the Antwerp Polyglot -- The Northern scholars : Guy Lefevre de la Boderie -- Plantin and the Antwerp Project -- The Polyglot : the Syriac New Testament and associated Kabbalistic material -- The Polyglot : the Censura -- The 1584 Paris Syriac New Testament -- Finale